2012
DOI: 10.1007/s10664-012-9221-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of individual factors impacting the effectiveness of requirements inspections: a replicated experiment

Abstract: Cataloged from PDF version of article.This paper presents a replication of an empirical study regarding the impact of\ud individual factors on the effectiveness of requirements inspections. Experimental replications\ud are important for verifying results and investigating the generality of empirical studies.\ud We utilized the lab package and procedures from the original study, with some changes and\ud additions, to conduct the replication with 69 professional developers in three different\ud companies in Turk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
14
0
3
Order By: Relevance
“…Several personal attributes may have a bearing on the effectiveness of any requirements-related task: experience [8], [4], [9], academic education [10], [11], cognitive capabilities [12] etc. One of the aspects that has been proposed to most influence an individual's effectiveness in requirements engineering activities is the knowledge of the problem domain [6], [13], [14], [15].…”
mentioning
confidence: 99%
“…Several personal attributes may have a bearing on the effectiveness of any requirements-related task: experience [8], [4], [9], academic education [10], [11], cognitive capabilities [12] etc. One of the aspects that has been proposed to most influence an individual's effectiveness in requirements engineering activities is the knowledge of the problem domain [6], [13], [14], [15].…”
mentioning
confidence: 99%
“…To that end, researchers have tried to understand the impact of individual factors on inspection performance by experimenting with educational background and level oftechnical degree [9,11]. However, empirical results at major software organizations showed that non-technical inspectors detected significantly larger number of faults recorded in NL requirements documents as compared to the people with higher technical degrees [2,9]. These results led us to hypothesize that inspector's ability to detect faults during inspection may be affected by the ways they perceive and process information known as Learning Styles (LS).…”
mentioning
confidence: 99%
“…Existen diversas características personales que pueden influir en la efectividad de cualquier tarea relacionada con requisitos: la experiencia (Agarwal & Tanniru, 1990;Niknafs & Berry, 2012), formación académica (Albayrak & Carver, 2014;Carrizo, Dieste, & Juristo, 2014), capacidades cognitivas (Pitts & Browne, 2004), el conocimiento del dominio (Christel & Kang, 1992;Loucopoulos & Karakostas, 1995;Niknafs & Berry, 2012;Niknafs & Berry, 2013;Young, 2002;Zowghi & Coulin, 2005), entre otras.…”
Section: Importancia De La Investigaciónunclassified
“…Por ejemplo, uno de los pocos trabajos existentes es el estudio empírico acerca del efecto de la formación académica en la efectividad de la actividad de inspección de requisitos realizado por Carver, Nagappan y Page (2008) (así como su replicación posterior reportada en (Albayrak & Carver, 2014)). Los resultados de ambos estudios ponen de manifiesto un efecto negativo de la formación académica en la efectividad, esto es, los sujetos sin formación académica en informática resultaron más efectivos que los sujetos con formación.…”
Section: Efecto De La Formación Académicaunclassified
See 1 more Smart Citation